Accumulation of advanced oxidative protein products exacerbate satellite glial cells activation and neuropathic pain - Chen Tu; Shi-Cheng Wang; Meng-Xuan Dai; Si-Qi Lai; Zhi-Wei Huang; Yong-Peng Yu; Yun-Biao Chen; Ji-Huan Zeng; Liang Wang; Zhao-Ming Zhong (Molecular Medicine)
Abstract Background Neuropathic pain (NP) is a debilitating condition caused by lesion or dysfunction in the somatosensory nervous system. Accumulation of advanced oxidation protein products (AOPPs) is implicated in mechanical hyperalgesia. However, the effects of AOPPs on NP remain unclear. Methods A rat model of NP was established by chronic constriction injury (CCI) and employed to evaluate the changes of mechanical withdrawal threshold, thermal and cold withdrawal latency, as well as AOPPs levels. The effects of AOPPs on the activation of satellite glial cells (SGCs) in the dorsal root ganglion (DRG), receptor for advanced glycation end-products (RAGE) expression, and NF-κB signaling pathway activation were also investigated using western blotting, immunofluorescence, and the Fluo4-AM fluorescence probe for calcium signaling. Additionally, oxidative stress levels and inflammatory cytokine production in SGCs, triggered by AOPPs exposure, were measured through the DCFH-DA probe for ROS detection and ELISA kits for cytokine quantification. Results CCI significantly elevated the AOPPs levels in the plasma and sciatic nerve and caused AOPPs accumulation in the DRG. Exogenous AOPPs activated SGCs, increased reactive oxygen species and inflammatory response, upregulated the RAGE, and activated NF-κB signaling. The RAGE inhibitor FPS-ZM1 effectively inhibited AOPPs-induced SGC activation. Additionally, AOPPs intervention worsened CCI-induced hyperalgesia and neuroinflammation in vivo. Conclusion These results indicate that AOPPs exacerbate the SGC activation and NP following nerve injury, and AOPPs accumulation might play an important role in the pathogenesis of NP.